2021
DOI: 10.33146/2307-9878-2021-1(91)-136-140
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Sports Industry Development and Economic Growth in China

Abstract: With the development of economy, people's pursuit of quality of life is increasing day by day, which lays a foundation for the development of sports industry in China. For example, in some western developed countries, the contribution of sports industry to economy has far exceeded that of traditional industry and become a new growth point of economic development. Although China's sports industry has made certain development, it is still in its infancy. Compared with the western developed countries, the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to the National Bureau of Statistics of China, the Chinese GDP was 471.564 billion yuan in 2011. GDP had reached 14.6 trillion yuan by 2020, accounting for 17.5% of global GDP [12]. After America, second place.…”
Section: Chinese Rapid Economic Developmentmentioning
confidence: 99%
“…According to the National Bureau of Statistics of China, the Chinese GDP was 471.564 billion yuan in 2011. GDP had reached 14.6 trillion yuan by 2020, accounting for 17.5% of global GDP [12]. After America, second place.…”
Section: Chinese Rapid Economic Developmentmentioning
confidence: 99%
“…Kharchenko and Ziming believe that sports industry consumption can drive the development of many related industries and use measurement dynamic technology to study the interdependence between economy and sports industry and use this method to formulate sports marketing strategies. As an emerging industry, sports industry has the potential to become a new growth point of the national economy because it can attract a large amount of investment and consumption, and the growth rate of added value of sports industry has significantly exceeded the growth rate of GDP [4]. Mallick et al studied from the perspective of cost of sports products and found that the lower the unit cost of sports products, the lower the price of products provided by the sports industry.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, another dimension, namely knowledge, can be integrated through sports, and education which aims to educate the nation's life (Bendíková & Dobay, 2017). Furthermore, the dimensions of a decent standard of living, obviously apart from healthy living, people can take advantage of sports from other elements, such as the sports industry that supports the economy (Kharchenko & Ziming, 2021;Millington et al, 2022), so that in the end it will have an impact on increasing a more decent life.…”
Section: Community Sports Development For Development Through Sportsmentioning
confidence: 99%